In Situ Growth of Ultrathin Ni(OH)2 Nanosheets as Catalyst for Electrocatalytic Oxidation Reactions. Issue 14 (9th June 2021) - Zhang, Jifang; Gong, Wanbing; Yin, Huajie; Wang, Dongdong; Zhang, Yunxia; Zhang, Haimin; Wang, Guozhong; Zhao, Huijun
Abstract: Development of electrocatalysts that are capable of efficiently oxidizing biomass‐derived 5‐hydroxymethylfurfural (HMF) into 2, 5‐furandicarboxylic acid (FDCA) is critically important for production of degradable plastics via non‐fossil routes. In this study, a facile and scalable immersion synthetic approach has been developed to grow ultrathin nickel hydroxide nanosheets in situ on commercial nickel foam (Ni(OH)2 /NF) as an anode for the electrocatalytic oxidation of HMF to FDCA with complete HMF conversion, 100 % FDCA yield, and >99 % faradaic efficiency at 1.39 V (vs. RHE) within 90 min. Mechanistic studies reveal that the initial oxidation of HMF takes place at the carbonyl group and FDCA is generated through two further oxidation steps. Impressively, the synthesized Ni(OH)2 /NF can also be used to electrocatalytically oxidize other alcohol/aldehyde‐containing compounds to the targeted products in alkaline medium with 100 % yield and >94 % faradaic efficiency under a low oxidation potential of 1.39 V (vs. RHE) within short reaction times. Abstract : Keep it 100 : A facile immersion approach has been developed to grow ultrathin nickel hydroxide nanosheets, which show excellent performance as the anode for electrocatalytic oxidation of 5‐hydroxymethylfurfural to 2, 5‐furandicarboxylic acid with 100 % yield and essentially 100 % faradaic efficiency under a low potential within a short reaction time.